Application of Systematic Approach for Fast Oil Production Enhancement-Case Studies - Motahari, Seyed Mahdia; Pari, Mahdi Nadri (Journal of Petroleum Research and Studies, 2014)
Full field studies and master development plans are time consuming and expensive tasks for any company to find optimum improved oil recovery method. Fast oil production enhancement is a method applied over existing assets resulting in fast increase in oil production in less expensive way. This approach consists of five steps as identification of source of production decline problem through evaluation of diagnostic tests, prioritizing different solutions for treating the problem, conceptual integrated modeling of reservoir and wells, production network optimization and economic analysis. In this paper we elaborate and implement these five steps in an Iranian Oil Field with twenty wells. Firstly; we found that the production decline is due to poor well cleaning after stimulation and work over operation and also reservoir pressure decline leading to not having sufficient energy to push oil to the surface. Secondly; based on specifications of each well and pre-determined screening criteria; artificial lift methods were prioritized followed thirdly by conceptual modeling of first ranked artificial lift method which was electric submersible pump for first ranked wells. The fourth step was optimization of production network through sequential quadratic programming and lastly probabilistic economic analysis based on different ESP time to failure. The result of this study shows viability of application of ESP in this field in fast way.